2021
DOI: 10.18662/rrem/13.4/468
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a New Format of Projects Method in Blended Learning Conditions Studying Disciplines of the Pedagogical Cycle

Abstract: The paper discusses the main issues of organizing the learning process based on the gamification. The publication analyzes the main provisions of the application of elements of gamification in the process of teaching students. The study proposes to consider gamification as a new format of the project method in the context of blended learning in the study of disciplines of the pedagogical cycle by students of humanitarian and natural specialties. We analyzed the main didactic Classcraft platform capabilities. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…*Rapid digitization in the ongoing era requires individuals and institutions to remain updated, especially educational institutions. The educational sector has become in need of new and appropriate tools to access modern content faster and more effectively (Nalyvaiko et al, 2021). Admittedly, an appropriate learning environment must be linked to the objectives and compatibility between the characteristics of such an environment with the learning objectives to achieve the desired goal (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…*Rapid digitization in the ongoing era requires individuals and institutions to remain updated, especially educational institutions. The educational sector has become in need of new and appropriate tools to access modern content faster and more effectively (Nalyvaiko et al, 2021). Admittedly, an appropriate learning environment must be linked to the objectives and compatibility between the characteristics of such an environment with the learning objectives to achieve the desired goal (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the scientific literature has shown that the problem of the quality of education has become highly relevant since the onset of the pandemic (Chick et al, 2020;Elumalai et al, 2021). Scientists consider various aspects of learning during a pandemic and online learning in general: satisfaction with the online learning process (Chen et al, 2020); adaptation and communication in the digital space (Dorsi et al, 2021;Plass & Pawar, 2020a;2020b;Vanherle, 2021); motivation in online learning environments (Dragon, 2019); new forms of forced online interaction (Bardus, et al, 2021;Nalyvaiko, et al 2021;Plass & Pawar, 2020a;Serhan, 2020); comparison of online and offline learning (Goss et al, 2021); monitoring in higher education (Lane & D'Mello, 2018); risks and prospects of forced distance learning (Neuwirth et al, 2021;Zhu & Liu, 2020); involvement in the learning process (Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%